Installing and thereafter removing an aberrant prosthesis elicited opposite remodelling responses in growing mouse temporomandibular joints. (1st May 2015) - Zhang, H.‐Y.; Liu, Y.‐D.; Yang, H.‐X.; Zhang, M.; Liao, L.‐F.; Wan, X.‐H.; Wang, M.‐Q.
Summary Temporomandibular joint (TMJ) displays a high remodelling capability. The current purpose was to investigate the differences between mandibular condylar remodelling responses of growing mice to installation and removal of unilateral anterior crossbite (UAC) prosthesis. Twenty‐four mice were divided into one mock control group and two UAC groups. Unilateral anterior crossbite was created by installing a pair of prosthesis to left‐side maxillary and mandibular incisors. Unilateral anterior crossbite was removed in removal group at 3 weeks but remained in UAC group. Temporomandibular joints were sampled at 7 weeks. Changes in condylar cartilage and subchondral bone were assessed by histology and in vivo micro‐CT. Real‐time PCR and immunohistochemistry were performed to evaluate expression changes in ADAMTS‐5, MMP‐3, MMP‐9, MMP‐13, IL‐1, TNF‐α, OPG and RANKL. Statistical analysis was performed at α = 0·05. Temporomandibular joint cartilage degradation was induced by UAC as previously reported but was reversed by removal of UAC. The dropped cartilage thickness, chondrocyte number and collagen II‐positive area, the increased expression levels of Adamts‐5, Mmp3, 9, 13, Tnf‐α and Il‐1β in cartilage, the decreased ratio of OPG/RANKL in both condylar cartilage and subchondral bone, the loss of TMJ subchondral bone and the increase in the TRAP‐positive cells in subchondral bone were all reversed in the removal group (P < 0·05). The growing mouse TMJ condyle displays a high remodelling capability which can be degenerative and rehabilitative, respectively, in response to placement and thereafter removal of the aberrant prosthesis. Eliminating aberrant prosthesis is helpful to promote the degraded condyle to recover.